Metallic Stent Mesh Coated with Silver Nanoparticles Suppresses Stent-Induced Tissue Hyperplasia and Biliary Sludge in the Rabbit Extrahepatic Bile Duct - Wooram Park; Kun Yung Kim; Jeon Min Kang; Dae Sung Ryu; Dong-Hyun Kim; Ho-Young Song; Seong-Hun Kim; Seung Ok Lee; Jung-Hoon Park (MDPI AG, 2020)
Recent therapeutic strategies to suppress restenosis after biliary stent placement are insufficient. Here, we demonstrate the usefulness of a self-expandable metal stent (SEMS), a stent mesh coated with silver nanoparticles (AgNPs), for suppression of both stent-induced tissue hyperplasia and biliary sludge formation in the rabbit bile duct. The AgNP-coated SEMSs were prepared using a simple bio-inspired surface modification process. Then, the prepared SEMSs were successfully placed in 22 of 24 rabbits. Sludge formation in the AgNP-coated SEMS groups was significantly decreased compared to the control group on gross findings. Cholangiographic and histologic examinations demonstrated significantly decreased tissue hyperplasia in the AgNP-coated SEMS groups compared with the control group (p < 0.05 for all). There were no differences between the AgNP-coated SEMS groups (p > 0.05 for all). However, in the group coated with the greatest concentration of AgNPs (Group D), submucosal fibrosis was thicker than in the other AgNP-coated groups (p < 0.05 for all). The AgNP-coated metallic stent mesh significantly suppressed stent-induced tissue hyperplasia and biliary sludge formation in the rabbit bile duct. Taken together, the AgNP coating strategy developed in this study could be widely utilized in non-vascular medical devices for anti-bacterial and anti-inflammatory responses.